Engineering in K-12 Education: Understanding the Status and Improving the Prospects - National Academy of Engineering; National Research Council (The National Academies Press, 2009)
Engineering education in K-12 classrooms is a small but growing phenomenon that may have implications for engineering and also for the other STEM subjects2014science, technology, and mathematics. Specifically, engineering education may improve student learning and achievement in science and mathematics, increase awareness of engineering and the work of engineers, boost youth interest in pursuing engineering as a career, and increase the technological literacy of all students. The teaching of STEM subjects in U.S. schools must be improved in order to retain U.S. competitiveness in the global economy and to develop a workforce with the knowledge and skills to address technical and technological issues. Engineering in K-12 Education reviews the scope and impact of engineering education today and makes several recommendations to address curriculum, policy, and funding issues. The book also analyzes a number of K-12 engineering curricula in depth and discusses what is known from the cognitive sciences about how children learn engineering-related concepts and skills. Engineering in K-12 Education will serve as a reference for science, technology, engineering, and math educators, policy makers, employers, and others concerned about the development of the country's technical workforce. The book will also prove useful to educational researchers, cognitive scientists, advocates for greater public understanding of engineering, and those working to boost technological and scientific literacy.

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.

Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States - National Research Council (The National Academies Press, 2005)
Policy Implications of International Graduate Students and Postdoctoral Scholars in the United States explores the role and impact of students and scholars on US educational institutions and the US economy. The nation has drawn increasingly on human resources abroad for its science and engineering workforce. However, competition for talent has grown as other countries have expanded their research infrastructure and created more opportunities for international students. The report discusses trends in international student enrollments, stay rates, and examines the impact of visa policies on international mobility of the highly skilled.

Successful STEM Education: A Workshop Summary - National Research Council (The National Academies Press, 2011)
What students learn about the science disciplines, technology, engineering, and mathematics during their K-12 schooling shapes their intellectual development, opportunities for future study and work, and choices of career, as well as their capacity to make informed decisions about political and civic issues and about their own lives. Most people share the vision that a highly capable STEM workforce and a population that understands and supports the scientific enterprise are key to the future place of the United States in global economics and politics and to the well-being of the nation. Indeed, the solutions to some of the most daunting problems facing the nation will require not only the expertise of top STEM professionals but also the wisdom and understanding of its citizens. Although much is known about why schools may not succeed, it is far less clear what makes STEM education effective. Successful STEM Education: A Workshop Summary discusses the importance of STEM education. The report describes the primary types of K-12 schools and programs that can support successful education in the STEM disciplines and examines data and research that demonstrate the effectiveness of these school types. It also summarizes research that helps to identify both the elements that make such programs effective and what is needed to implement these elements.

Research Universities and the Future of America: Ten Breakthrough Actions Vital to Our Nation's Prosperity and Security - National Research Council (The National Academies Press, 2012)
Research Universities and the Future of America presents critically important strategies for ensuring that our nation's research universities contribute strongly to America's prosperity, security, and national goals. Widely considered the best in the world, our nation's research universities today confront significant financial pressures, important advances in technology, a changing demographic landscape, and increased international competition. This report provides a course of action for ensuring our universities continue to produce the knowledge, ideas, and talent the United States needs to be a global leader in the 21st century. Research Universities and the Future of America focuses on strengthening and expanding the partnership among universities and government, business, and philanthropy that has been central to American prosperity and security. The report focuses on the top 10 actions that Congress, the federal government, state governments, research universities, and others could take to strengthen the research and education missions of our research universities, their relationships with other parts of the national research enterprise, and their ability to transfer new knowledge and ideas to those who productively use them in our society and economy. This report examines trends in university finance, prospects for improving university operations, opportunities for deploying technology, and improvement in the regulation of higher education institutions. It also explores ways to improve pathways to graduate education, take advantage of opportunities to increase student diversity, and realign doctoral education for the careers new doctorates will follow. Research Universities and the Future of America is an important resource for policy makers on the federal and state levels, university administrators, philanthropic organizations, faculty, technology transfer specialists, libraries, and researchers.

Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
In a world where advanced knowledge is widespread and low-cost labor is readily available, U.S. advantages in the marketplace and in science and technology have begun to erode. A comprehensive and coordinated federal effort is urgently needed to bolster U.S. competitiveness and pre-eminence in these areas. This congressionally requested report by a pre-eminent committee makes four recommendations along with 20 implementation actions that federal policy-makers should take to create high-quality jobs and focus new science and technology efforts on meeting the nation's needs, especially in the area of clean, affordable energy: 1) Increase America's talent pool by vastly improving K-12 mathematics and science education; 2) Sustain and strengthen the nation's commitment to long-term basic research; 3) Develop, recruit, and retain top students, scientists, and engineers from both the U.S. and abroad; and 4) Ensure that the United States is the premier place in the world for innovation. Some actions will involve changing existing laws, while others will require financial support that would come from reallocating existing budgets or increasing them. Rising Above the Gathering Storm will be of great interest to federal and state government agencies, educators and schools, public decision makers, research sponsors, regulatory analysts, and scholars.

S&T Strategies of Six Countries: Implications for the United States - National Research Council
An increase in global access to goods and knowledge is transforming world-class science and technology (S&T) by bringing it within the capability of an unprecedented number of global parties who must compete for resources, markets, and talent. In particular, globalization has facilitated the success of formal S&T plans in many developing countries, where traditional limitations can now be overcome through the accumulation and global trade of a wide variety of goods, skills, and knowledge. As a result, centers for technological research and development (R&D) are now globally dispersed, setting the stage for greater uncertainty in the political, economic, and security arenas. These changes will have a potentially enormous impact for the U.S. national security policy, which for the past half century was premised on U.S. economic and technological dominance. As the U.S. monopoly on talent and innovation wanes, arms export regulations and restrictions on visas for foreign S&T workers are becoming less useful as security strategies. The acute level of S&T competition among leading countries in the world today suggests that countries that fail to exploit new technologies or that lose the capability for proprietary use of their own new technologies will find their existing industries uncompetitive or obsolete. The increased access to information has transformed the 1950s' paradigm of \

Rising Above the Gathering Storm, Revisited: Rapidly Approaching Category 5 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In the face of so many daunting near-term challenges, U.S. government and industry are letting the crucial strategic issues of U.S. competitiveness slip below the surface. Five years ago, the National Academies prepared Rising Above the Gathering Storm, a book that cautioned: \

A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field. A Framework for K-12 Science Education outlines a broad set of expectations for students in science and engineering in grades K-12. These expectations will inform the development of new standards for K-12 science education and, subsequently, revisions to curriculum, instruction, assessment, and professional development for educators. This book identifies three dimensions that convey the core ideas and practices around which science and engineering education in these grades should be built. These three dimensions are: crosscutting concepts that unify the study of science through their common application across science and engineering; scientific and engineering practices; and disciplinary core ideas in the physical sciences, life sciences, and earth and space sciences and for engineering, technology, and the applications of science. The overarching goal is for all high school graduates to have sufficient knowledge of science and engineering to engage in public discussions on science-related issues, be careful consumers of scientific and technical information, and enter the careers of their choice. A Framework for K-12 Science Education is the first step in a process that can inform state-level decisions and achieve a research-grounded basis for improving science instruction and learning across the country. The book will guide standards developers, teachers, curriculum designers, assessment developers, state and district science administrators, and educators who teach science in informal environments.

Making Value for America: Embracing the Future of Manufacturing, Technology, and Work - National Academy of Engineering
Globalization, developments in technology, and new business models are transforming the way products and services are conceived, designed, made, and distributed in the U.S. and around the world. These forces present challenges - lower wages and fewer jobs for a growing fraction of middle-class workers - as well as opportunities for \

Rising to the Challenge: U.S. Innovation Policy for the Global Economy - National Research Council (The National Academies Press, 2012)
America's position as the source of much of the world's global innovation has been the foundation of its economic vitality and military power in the post-war. No longer is U.S. pre-eminence assured as a place to turn laboratory discoveries into new commercial products, companies, industries, and high-paying jobs. As the pillars of the U.S. innovation system erode through wavering financial and policy support, the rest of the world is racing to improve its capacity to generate new technologies and products, attract and grow existing industries, and build positions in the high technology industries of tomorrow. Rising to the Challenge: U.S. Innovation Policy for Global Economy emphasizes the importance of sustaining global leadership in the commercialization of innovation which is vital to America's security, its role as a world power, and the welfare of its people. The second decade of the 21st century is witnessing the rise of a global competition that is based on innovative advantage. To this end, both advanced as well as emerging nations are developing and pursuing policies and programs that are in many cases less constrained by ideological limitations on the role of government and the concept of free market economics. The rapid transformation of the global innovation landscape presents tremendous challenges as well as important opportunities for the United States. This report argues that far more vigorous attention be paid to capturing the outputs of innovation - the commercial products, the industries, and particularly high-quality jobs to restore full employment. America's economic and national security future depends on our succeeding in this endeavor.

Standards for K-12 Engineering Education? - National Research Council (The National Academies Press, 2010)
The goal of this study was to assess the value and feasibility of developing and implementing content standards for engineering education at the K-12 level. Content standards have been developed for three disciplines in STEM education–science, technology, and mathematic–but not for engineering. To date, a small but growing number of K-12 students are being exposed to engineering-related materials, and limited but intriguing evidence suggests that engineering education can stimulate interest and improve learning in mathematics and science as well as improve understanding of engineering and technology. Given this background, a reasonable question is whether standards would improve the quality and increase the amount of teaching and learning of engineering in K-12 education. The book concludes that, although it is theoretically possible to develop standards for K-12 engineering education, it would be extremely difficult to ensure their usefulness and effective implementation. This conclusion is supported by the following findings: (1) there is relatively limited experience with K-12 engineering education in U.S. elementary and secondary schools, (2) there is not at present a critical mass of teachers qualified to deliver engineering instruction, (3) evidence regarding the impact of standards-based educational reforms on student learning in other subjects, such as mathematics and science, is inconclusive, and (4) there are significant barriers to introducing stand-alone standards for an entirely new content area in a curriculum already burdened with learning goals in more established domains of study.

Report of a Workshop on Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs for the U.S. Department of Defense and the U.S. Defense Industrial Base - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
Report of a Workshop on Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs for the U.S. Department of Defense and the U.S. Defense Industrial Base is the summary of a workshop held August 11, 2011, as part of an 18-month study of the issue. This book assesses the STEM capabilities that the Department of Defense (DOD) needs in order to meet its goals, objectives, and priorities; to assess whether the current DOD workforce and strategy will meet those needs; and to identify and evaluate options and recommend strategies that the department could use to help meet its future STEM needs.

Is America Falling Off the Flat Earth? - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2007)
The aviation and telecommunication revolutions have conspired to make distance increasingly irrelevant. An important consequence of this is that US citizens, accustomed to competing with their neighbors for jobs, now must compete with candidates from all around the world. These candidates are numerous, highly motivated, increasingly well educated, and willing to work for a fraction of the compensation traditionally expected by US workers. If the United States is to offset the latter disadvantage and provide its citizens with the opportunity for high-quality jobs, it will require the nation to excel at innovation–that is, to be first to market new products and services based on new knowledge and the ability to apply that knowledge. This capacity to discover, create and market will continue to be heavily dependent on the nation's prowess in science and technology. Indicators of trends in these fields are, at best, highly disconcerting. While many factors warrant urgent attention, the two most critical are these: (1) America must repair its failing K-12 educational system, particularly in mathematics and science, in part by providing more teachers qualified to teach those subjects, and (2) the federal government must markedly increase its investment in basic research, that is, in the creation of new knowledge. Only by providing leading-edge human capital and knowledge capital can America continue to maintain a high standard of living–including providing national security–for its citizens.

Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future: Summary of a Convocation - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2009)
Rising Above the Gathering Storm Two Years Later: Accelerating Progress Toward a Brighter Economic Future summarizes a convocation held in April 2008 to commemorate the release of the original Gathering Storm report. The convocation featured participation by Members of Congress, Cabinet Secretaries, leaders from industry and academia, and other experts. The discussions reviewed progress made thus far in implementing the Gathering Storm recommendations to strengthen K-12 education in math and science, research, higher education, and the environment for innovation. Participants also noted that much additional work is needed to ensure that America remains a leader in science and engineering in the long term.